Applying the Berberine-Pretreated Filter for Inactivating Bioaerosols - Hsu, Ying-Fang; Huang, Hsiao-Chien; Yang, Shinhao (Journal of Membrane and Separation Technology, 2017)
This work considers the effects of using the berberine pretreated filters (BPFs) as the antiseptic filters on the bioaerosol penetration. Two concentrations of berberine solutions were used to coat on the polypropylene fibrous filter. The Escherichia coli (E. coli), and Bacillus subtilis (B. subtilis) bioaerosols were generated using a Collison nebulizer, as the challenged bioaerosols. The effects of various factors, including the face velocity and the relative humidity on the bioaerosol collection characteristics were evaluated. Experimental results suggested the pretreatment of berberine did have an antiseptic effect on bacteria bioaerosol and increase the inactivation mechanism. The filter pretreated with a higher concentration of berberine has a stronger antiseptic effect on bioaerosols. The culturable survival of E. coli bioaerosols through the untreated filter, the 0.002 wt%, and 0.02 wt% BPFs are around 68%, 43% and 36%, respectively. In addition, the culturable survival of B. subtilis bioaerosols through the 0.002 wt%, and 0.02 wt% BPFs are around 66%, 51% and 43%, respectively. Moreover, the culturable survival of E. coli bioaerosol through the 0.002 wt% BPFs increased from 43% to 54% as the face velocity increased from 10 to 30 cm/s. These results indicated that the antiseptic of the BPFs decreased with face velocity.